2021
DOI: 10.1016/j.vph.2021.106857
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for ST2 as prognostic biomarker for COVID-19

Abstract: COVID-19 is a pandemic illness caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2). It has been estimated that 80% of subject infected are asymptomatic or have mild to moderate symptoms. Differently, in severe cases of COVID-19 cytokine storm, acute respiratory distress syndrome (ARDS), severe systemic inflammatory response and cardiovascular diseases were observed Even if all molecular mechanisms leading to cardiovascular dysfunction in COVID-19 patients remain to be clarified, the evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 94 publications
3
11
0
Order By: Relevance
“…The IL-33/ST2 axis might play a leading role in COVID-19 pathogenesis [32][33][34][35]. Although our study was not aimed to gain pathophysiological insight into COVID-19, our findings support this hypothesis.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The IL-33/ST2 axis might play a leading role in COVID-19 pathogenesis [32][33][34][35]. Although our study was not aimed to gain pathophysiological insight into COVID-19, our findings support this hypothesis.…”
Section: Discussionsupporting
confidence: 71%
“…sST2 has been shown to be elevated in patients with Kawasaki disease which, in addition, correlated with clinical worse course [40,41]. More importantly, cardiovascular co-morbidity, and more specifically HF, has been identified as a significant risk factor for COVID-19 severity and worse outcome [34,35,42]. sST2 is also an established prognosis maker in HF.…”
Section: Discussionmentioning
confidence: 99%
“…We found high concentrations of ST2 in the plasma of COVID-19 patients, which has been suggested to be related to endothelial or pneumocyte inflammation and damage [11]. We found that higher levels of ST2 were associated with mortality, which supports the prognostic value of this biomarker in COVID-19, as suggested elsewhere [22].…”
Section: Discussionsupporting
confidence: 87%
“…This gene has been known to be cardioprotective for myocardial functions and has been implicated with increased cardiomyocyte hypertrophy and ventricular fibrosis upon germline deletion of ST2 in mouse models. Furthermore, ST2 57 has also been tolled as a promising prognostic biomarker for COVID-19 58 with ST2 serum level suggested to be significantly increased in COVID-19 patients 59 , as opposed to the significant downregulation of IL1RL1 in COVID-19 heart samples .…”
Section: Resultsmentioning
confidence: 99%